A munkaerőpiac marketing alapú megközelítése = The marketing based approach to labour market - Chovan, Brigitta (Közép-Európai Közlemények, 2017)
The marketing based approach to labour markét dates back to the 90s in Hungary. Accordingly, we can relate to labour markét from the perspective of supply and demand. On the markét of products and Services equally, the goal is to seize the ”good customer”; this happens the same way in the world of work. Companies consider obtaining and preserving good workforce in possession of the appropriate competencies and achieving their identification with corporate culture a duty of key relevance. They try to attract new employees, talents by means of extemal labour markét recruitment, while within the internál labour markét companies wish to raise the commitment, motivation and performance of existing employees. The most valuable source of companies is the employee; therefore, to ensure the long term process of creating value, employment branding must be a crucial part of the HR strategy. Employer branding serves as a bridge between markét and humán resource goals.